International marketing in practice : a case study collection - Boulocher-Passet, Véronique (International cases in business and management, 2025)
International Marketing in Practice features select case studies relating to businesses from various markets and countries facing the challenges and decisions involved when undertaking international marketing.Across its four sections, the book examines how companies can overcome the challenges of connecting with potential customers in a foreign country through strategic choices around which markets to enter, identifying appropriate modes of entry, successfully adapting their marketing mix for these markets, and leveraging a country-of-origin strategy. The book showcases 11 unique and international case studies grounded in the experiences of real companies of varying sizes, operating in a range of industries. Each case features a case synopsis, learning objectives, a concise narrative, along with stimulating discussion questions for individual cases as well as each section. These compact case studies will enable students to apply concepts to situations in other organizations, thus strengthening their understanding and supporting learning.This exciting new text is designed as recommended reading on undergraduate and postgraduate International Marketing and International Business courses.For instructors who teach with the cases, there are accompanying teaching notes available online.